A prospective controlled investigation of the cognitive effects of amateur boxing. Issue 10 (October 1993) - Butler, R J; Forsythe, W I; Beverly, D W; Adams, L M
Abstract : Eighty six amateur boxers underwent a series of neuropsychological assessments on three occasions--pre bout, immediate post bout and follow up within two years; 31 water polo players and 47 rugby union players acted as controls. The neuropsychological tests were selected as being sensitive to subtle cognitive dysfunction and formed part of a battery of other neurological and ophthalmic assessments. No evidence of neuropsychological dysfunction due to boxing was found, either following a bout or a series of bouts at follow up. None of a range of parameters including number of previous contests, recovery from an earlier bout, number of head blows received during a bout and number of bouts between initial assessment and follow up, were found to be related to changes in cognitive functioning.